The effect of using contextual-based motion dynamics learning videos on Higher Order Thinking Skills (HOTS) - Utami, Nurdian Rahmah; Desnita, Desnita; Akmam, Akmam; Emiliannur, Emiliannur (Universitas Muhammadiyah Mataram, 2024)
21st century education requires students to master Higher Order Thinking Skills (HOTS). Based on a survey at SMAN 13 Padang, it is known that students' HOTS is still relatively low. One of the reasons is that the use of learning media has not facilitated students' HOTS. HOTS can be improved by using contextual-based learning videos and reinforced with problem-based learning models. This study aims to see the effect of using contextual-based motion dynamics learning videos on students' HOTS. This research is a pseudo-experimental research, posttest-only control design. The population of this research is the entire class XI Phase F SMAN 13 Padang in the 2023/2024 academic year studying physics. The sampling was done using purposive sampling technique. This study used class XI F3 as the experimental class and class XI F7 as the control class. The data in this study is HOTS data. The research instrument is a written test in the form of an essay totaling 6 questions. The results showed that the average HOTS in the experimental class was higher than the control class. The results of the hypothesis test in the form of a t test with a 5% level obtained t_count = 4,72 and dan t_table=1,997,, meaning that the price of t_count is in the H_o rejection area so that H_I is accepted at a real level of 0.05. Thus, it shows that there is an effect of using contextual-based motion dynamics learning videos on HOTS of SMA Negeri 13 Padang students.